Green Marketing Mix Based on Digitisation: A Strategy for Revitalising Micro, Small, and Medium Enterprises (MSMEs) in Medan City After the 2024 Elections - Aan, Aan Nurhadi; Siregar, Fhikry Ahmad Halomoan; Yanti, Tri Auri; Lubis, Irna Triannur (Yayasan Riset dan Pengembangan Intelektual, 2025)
This study aims to analyse the impact of the digitalisation-based Green Marketing Mix on the revitalisation strategy of Micro, Small, and Medium Enterprises (MSMEs) in Medan City after the 2024 elections. The research approach uses a quantitative method with a survey of 120 MSME actors, as well as qualitative depth through semi-structured interviews to obtain in-depth perspectives on the implementation of green digital strategies. The results show that the components of the Green Marketing Mix, including environmentally friendly products, pricing, digital promotion, and digital-based distribution, have a significant effect on MSME revitalisation, particularly in terms of increasing competitiveness, operational efficiency, and consumer engagement. Qualitative analysis reveals that marketing digitalisation enables MSMEs to penetrate broader markets, reduce costs, and strengthen their sustainable business image. These findings emphasise the importance of integrating green strategies and digitalisation as a solution for revitalising MSMEs after major political events, and provide practical implications for the development of government policies and business actors to improve local economic sustainability.